PENERAPAN METODE BERMAIN DAN BERCERITA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AWAL PADA ANAK USIA DINI - Nurindah Sumiar; Aufilana Rahmatika; Nihwan Nihwan (Institut Agama Islam Negeri Metro, 2020)
Early childhood in the range of 4-6 years who are not fond of reading so that researchers are interested in conducting classroom action research (CAR) on their students, especially group A students. the following results were obtained: (1) there was an increase in the quality of reading learning for group A RA Harapan Bangsa Sembego students, and (2) there was an increase in reading ability in group A RA Harapan Bangsa Sembego students. The improvement in the quality of reading learning and students' reading abilities can be seen in the following indicators: (a) students show an interest and enthusiasm in participating in the reading learning process, because the teacher indirectly provides information about the story material to be learned through question and answer activities, (b) students seem to pay attention to the lesson seriously and are seen to be active in teaching and learning activities, and (c) students 'reading ability has increased, this can be seen from the results of students' test scores in learning to read in the form of tests to retell the content of the story correctly which shows an increase from cycle I, II, and III. Keywords: Playing and Storytelling, Early Reading, Early Childhood